A relação entre environmental, social and governance (ESG), desempenho e risco: evidências em empresas latino-americanas e suas implicações regionais - Teixeira, Fabiana Sousa Ribeiro (2024)
This work seeks to investigate the impact of ESG on the performance and risk of companies in Latin America. Firstly, a bibliometric research was carried out to analyze, in the literature, how the characteristics of articles published on Environmental, Social and Corporate Governance (ESG) practices influence the market value of companies. The main results indicate that the majority of articles were published in 2023, with three authors, and that 65% of the published articles found evidence that proves the influence of ESG practices on the market value of companies; 25% of the articles demonstrated that there is influence, but with some conditions and, finally, in 10% of the articles, the authors did not find evidence to prove the influence of ESG practices on the market value of companies. In the second test, the impact of ESG on the performance of publicly traded Latin American companies was investigated, as well as its effect on market value and market risk. Data was collected from publicly traded Latin American companies published in the Thomson Reuters database from 2011 to 2022. To achieve the objective of this work, regression models were estimated on panel data as an econometric model. The results suggest that there was no evidence that ESG impacts the performance, value and risk of companies in Latin America. This result can be justified by the fact that investing in ESG can increase companies' operating costs in the short term, but the adoption of ESG practices can lead to significant financial benefits in the long term. As for regional implications, it is suggested that although ESG practices do not have immediate impacts on company performance, they can improve long-term results, including for companies located in the Triângulo Mineiro and Alto Paranaíba.